Applying Lean Principles to Improve or Efficiency - Vandale, Tanya (Operating Room Nurses Association of Canada Journal, 2021)
LEAN is a set of operating philosophies and methods that, when applied to the healthcare setting, can help create maximum value for patients by reducing waste and unnecessary waits. An emphasis is placed on the customers’ needs, employee involvement and continuous improvement.1For the purposes of this article the customer is the patient. In April 2017 the Adult Surgery Program at the IWK Health Centre was involved in a comprehensive initiative to help improve efficiency in the Adult Surgery OR. Using LEAN principles, the patient’s surgical journey was examined closely by a multidisciplinary team where, multiple initiatives were identified. One of the first initiatives explored was the turnaround time between OR cases. By integrating LEAN methods in workflow, improvements in turnaround times were recognized.